A CASE STUDY OF THE IMPACT OF DIGITAL-BASED TRAINING ON EMPLOYEE ABILITY IN ERA 5.0 - Deddy Novie Citra Arta (Jurnal Ekonomi, 2022)
Employees are a valuable asset to the company's success. To obtain competent employees, the company must conduct job training with the goal of increasing employee competency at work. With the rapid advancement of technology, it is hoped that employee training can keep up. This research was conducted on PT employees. Indonesia Telecommunications Industry (Persero) Bandung to determine whether or not job training has an effect on PT employees. Indonesian Telecommunications Industry The researchers used a descriptive quantitative method with 52 respondents from PT and data collection techniques such as interviews, observations, literature studies, and questionnaires. The Indonesian Telecommunication Industry and the data were processed using SPSS software version 26. The coefficient results show that if R Square is 39% or 0.390, it can be stated that digital-based training affects the ability of employees in the 5.0 era by 39%, and the remaining 61% is